The Effectiveness of Behavior Change Techniques Underpinning Psychological Interventions to Improve Glycemic Levels for Adults With Type 2 Diabetes: A Meta-Analysis - Upsher, Rebecca; Onabajo, Deborah; Stahl, Daniel; Ismail, Khalida; Winkley, Kirsty (Frontiers in Clinical Diabetes and Healthcare, 2021)
An existing systematic review and meta-analysis found a significant reduction in glycemic levels for adults with type 2 diabetes who received a psychological intervention over control conditions. To help develop effective interventions in the future, there is a need to understand the active ingredients which underpin these psychological interventions. We conducted a secondary meta-analysis including 67 randomized controlled trials (RCTs) reported in English. We reviewed the psychological intervention descriptions of the included studies of the existing review and extracted the behavior change techniques (BCTs) according to the BCT taxonomy (BCTTv1). We also extracted information on primary behavioral target versus primary outcome, and presence of fidelity assessment. The most frequent BCTs across RCTs were ‘social support (unspecified)’ (n=50), ‘problem solving’ (n=38) and ‘goal setting (behavior’) (n=30). These BCTs were independently associated with a significant reduction in glycemic levels (HbA1c) compared to control conditions, but not significantly different from studies that did not include these BCTs. Meta-regressions revealed no significant associations between HbA1c, and psychological intervention category (counselling versus cognitive behavioral therapy interventions) (p=0.84), frequency of BCTs per psychological intervention (p=0.29), primary behavioral target versus primary outcome (p=0.48), or presence of fidelity assessment (p=0.15). Social support (unspecified), problem solving, and goal setting (behavior) could be useful BCTs to develop psychological interventions for people with type 2 diabetes to improve glycemic levels. However, more research is required to understand which combination of individual BCTs are most effective for this population. Systematic Review Registration Registered with the international prospective register of systematic reviews registration (PROSPERO) CRD42016033619.